A Conceptual framework of living labs for people: Fostering innovations for low-emissions food systems and social equity - Nehring, Ryan (CGIAR, 2023)
Presentations prepared by Ryan Nehring (IFPRI) for: - The Tropentag Conference in Berlin, Germany (Sept. 20-22) - The Adaptation Futures Side Event: International Forum on Agroecosystem Living Labs in Montreal, Canada (Oct. 3-6) - The Zhejiang University of Finance and Economics (Oct. 17)